Operationalizing a learning health system: A self‐assessment tool for interprofessional teams - Victor C. Rentes; Claire Kalpakjian; Anne Sales; Andrew Krumm (Learning Health Systems, 2025)
Abstract Background The operationalization of learning health system (LHS) principles remains challenging, with minimal guidance currently available to support interprofessional teams on the ground. Consequently, LHS initiatives often fall short of their intended objectives, resulting in wasted resources, delays, and mounting frustration among key stakeholders. Methods To bridge this gap, we used design science and participatory action research to co‐develop an operational roadmap for interprofessional LHS teams. Data sources for roadmap design included quantitative and qualitative feedback from interprofessional stakeholders (n = 20) from an academic health system and a pragmatic literature review. Using these data sources, we conducted three design iterations until a final version was reached. Results The resulting roadmap specifies processes to be performed during project‐based LHS initiatives, and provides a self‐assessment tool that enables team members to quantitatively evaluate progress. For generalizability and standardization across settings, we used clinically neutral terminology to describe all elements in the roadmap. We demonstrated content validity through multiple rounds of data collection and analyses with stakeholders. A simulated demonstration is provided to illustrate how the roadmap may be used for team assessments in practice. Conclusions Participants considered the roadmap to be an effective tool to assist project management and highly useful for evaluating teams' progress for planning and communication purposes. As a reference model, the roadmap may be re‐utilized across multiple LHS initiatives in any given health system to standardize and streamline LHS development. This research was conducted within a single department in an academic health system, and future research is needed to assess the roadmap's generalizability in other settings. To facilitate development of similar or complementary instruments, the detailed design methodology used in this research may be replicated and/or tailored in other contexts.